Arctium Species Secondary Metabolites Chemodiversity and Bioactivities - Wang, Dongdong; Bădărau, Alexandru Sabin; Swamy, Mallappa Kumara; Shaw, Subrata; Maggi, Filippo; da Silva, Luiz Everson; López, Víctor; Yeung, Andy Wai Kan; Mocan, Andrei; Atanasov, Atanas G. (Frontiers in Plant Science, 2019)
Arctium species are known for a variety of pharmacological effects due to their diverse volatile and non-volatile secondary metabolites. Representatives of Arctium species contain non-volatile compounds including lignans, fatty acids, acetylenic compounds, phytosterols, polysaccharides, caffeoylquinic acid derivatives, flavonoids, terpenes/terpenoids and volatile compounds such as hydrocarbons, aldehydes, methoxypyrazines, carboxylic and fatty acids, monoterpenes and sesquiterpenes. Arctium species also possess bioactive properties such as anti-cancer, anti-diabetic, anti-oxidant, hepatoprotective, gastroprotective, antibacterial, antiviral, antimicrobial, anti-allergic and anti-inflammatory effects. This review aims to provide a complete overview of the chemistry and biological activities of the secondary metabolites found in therapeutically used Arctium species. Summary of pharmacopoeias and monographs contents indicating the relevant phytochemicals and therapeutic effects are also discussed, along with possible safety considerations.